Height velocity and skeletal maturation in elite female rhythmic gymnasts - Georgopoulos, N. A.; Markou, K. B.; Theodoropoulou, A.; Vagenakis, G. A.; Benardot, D.; Leglise, M.; Dimopoulos, J. C.; Vagenakis, A. G. (The Journal of Clinical Endocrinology & Metabolism, 2001)
Rhythmic gymnasts performing under conditions of high intensity are exposed to particularly high levels of psychological stress and intense physical training, factors that can contribute to the observed delay in skeletal maturation and pubertal development, and alter optimal growth. The study was conducted in the field, during the International, European, and World Rhythmic Sports Gymnastics Championships of the years 1997-2000, and included 104 elite female rhythmic gymnasts, aged 12-23 yr. The study included height and weight measurements, estimation of body fat and skeletal maturation, and registration of parental height. Height, weight, target height, and predicted adult height were expressed as the SD score of the mean height and weight for age, according to Tanner`s standards. Gymnasts were taller and thinner than average for age, with height velocity SD score for each age group above the 50th percentile for all age groups (n = 140, mean = 1.9 ± 2.5). Interestingly, although height velocity in normal girls comes to an end by the age of 15, in our examined rhythmic gymnasts it continues up to the age of 18. There was a delay of skeletal maturation of 1.8 yr (n = 72, r = 0.730, P < 0.001), compensated by an acceleration of height velocity toward the end of puberty. The final adult height was identical to the estimated predicted height at first evaluation, and significantly higher than the genetically determined target height (n = 35, r = 0.58, P < 0.001), denoting that genetic predisposition to final height is not only achieved, but even exceeded. Using multiple regression analysis, target height was the only independent parameter that has been proven to influence positively the height velocity SD score (b = 0.233, t = 2.215, P = 0.029), denoting that genetic predisposition remains the main driving force for the observed efficient catch up growth. In conclusion, the elite rhythmic gymnasts compensate for their loss of pubertal growth spurt by a late acceleration of linear growth. Despite the delay in skeletal maturation, genetic predisposition of growth is not only preserved, but even exceeded.